État de lieu des données internationales sur les inégalités de genre dans le développement international - Machkouri, Zora Ait El; Bourassa-Dansereau, Caterine; Langevin, Marie (Cahiers de recherche OFDIG, 2022)
Ce cahier présente un premier état des lieux du développement inclusif par le genre (DIG) et brosse le portrait des sources de données internationales et institutionnelles existantes et accessibles au sujet du développement inclusif afin d’outiller l’Observatoire et de soutenir ses partenaires dans leur volonté de se saisir de cette problématique de l’égalité et de participer concrètement aux défis qui en découlent. En répertoriant les sources de données existantes, en analysant leurs caractéristiques et leurs lacunes ainsi qu’en identifiant les angles morts dans la couverture des dimensions inégalitaires persistantes au sein des secteurs clés du DIG (milieux économiques, systèmes éducatifs, domaine de l’enseignement supérieur et de la recherche ), nous cernons des enjeux qui sont au cœur de la mission de l’Observatoire.
Keywords: 2000 à aujourd'hui; OFDIG; afrique; amériques; approches et analyses; discipline; développement durable; empowerment; féminisme décolonial; genre; identités LGBTQIA2+; inégalités; point de vue situé; périodes historiques; ressource en ligne; régions géographiques; statistiques; systèmes d'oppressions; thématiques

Race, gender, class, sexuality (RGCS) and hypertension - Veenstra, Gerry (Social Science & Medicine, 2013)
Informed by intersectionality theory, a tradition that theorizes intersecting power relations of racism, patriarchy, classism and heterosexism, this paper investigates the degree to which race, gender, class and sexuality manifest distinct and interconnected associations with self-reported hypertension in nationally-representative survey data from Canada. Binary logistic regression is used to model the main effects of, and interactions between, race, gender, education, household income and sexual orientation on hypertension, controlling for age, using data from the 2003 Canadian Community Health Survey (n = 90,310). From a main effects (‘additive’) perspective, Black respondents, respondents with less than high school and poorer respondents were significantly more likely than White respondents, university-educated Canadians and wealthier Canadians, respectively, to report hypertension. However, the interactive models indicate that the additive models were poor predictors of hypertension for wealthy Black men, wealthy South Asian women, women with less than a high school diploma and wealthy bisexual respondents, who were more likely than expected to report hypertension, and for poor Black men, poor South Asian women, poor South Asian men and women with a university degree, who were less likely than expected to report hypertension. It appears that, with regard to blood pressure at least, Canadians experience the health effects of education differently by their genders and the health effects of income differently by their identities defined at the intersection of race and gender. This study provides empirical support for the intersectional approach to cardiovascular health inequalities by demonstrating that race, gender, class and sexuality cannot be disentangled from one another as predictors of hypertension.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; discipline; hétérosexisme; intersectionnalité; médecine; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé cardiovasculaire; sciences; sexisme; systèmes d'oppressions; thématiques

Corps en tous genres : la dualité des sexes à l'épreuve de la science - Fausto-Sterling, Anne (Bibliotheque de l'IEC, 2012)
« Il y a deux sexes ! » Ce serait un fait de nature. La biologiste Anne Fausto-Sterling défait cette fausse évidence du sens commun, fut-il scientifique. N’y en aurait-il pas cinq, voire plus ? Ironique, cette proposition n’en est pas moins sérieuse : pour les intersexes, ni tout à fait garçons ni vraiment fille, il en va de leur vie. Va-t-on les faire entrer de force, par la chirurgie, dans l’une ou l’autre catégorie ? Et, quand ils envoient des messages différents, qui, des chromosomes, des hormones, du cerveau ou du squelette, a le dernier mot ? L’enjeu, ce sont les exceptions mais aussi la règle, à savoir tout le monde ! Le partage entre deux sexes est toujours une opération sociale. C’est bien la société qui tranche dans les variations attestées pour donner un sexe au corps. Et, quand le médecin ou le savant parlent de sexe, ou de sexualité, c’est encore la société que l’on entend. Loin d’être neutre, la science est donc toujours située : telle est l’une des leçons de cet ouvrage, devenu un classique depuis sa publication aux Etats-Unis en 2000. La critique du biologisme par une scientifique du sérail trouble nos oppositions convenues –entre genre (social) et sexe (biologique), entre culture et nature. Ainsi ne pourra-t-on plus dire qu’il faut choisir entre féminisme et science. Gai savoir que celui offert par ce livre illustré avec humour et érudition : la biologie, c’est bien la politique continuée par d’autres moyens.
Keywords: 1900-1999; LGBTQIA2+; amériques; biologie; cours; cycles supérieurs; discipline; fem1000; fem7000; identités LGBTQIA2+; lit3220; premier cycle; psy4910; périodes historiques; régions géographiques; sciences humaines; sciences sociales; sexes; thématiques; états-unis

Queer Diagnoses: Parallels and Contrasts in the History of Homosexuality, Gender Variance, and the Diagnostic and Statistical Manual - Drescher, Jack (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2010)
The American Psychiatric Association (APA) is in the process of revising its Diagnostic and Statistical Manual (DSM), with the DSM-V having an anticipated publication date of 2012. As part of that ongoing process, in May 2008, APA announced its appointment of the Work Group on Sexual and Gender Identity Disorders (WGSGID). The announcement generated a flurry of concerned and anxious responses in the lesbian, gay, bisexual, and transgender (LGBT) community, mostly focused on the status of the diagnostic categories of Gender Identity Disorder (GID) (for both children and adolescents and adults). Activists argued, as in the case of homosexuality in the 1970s, that it is wrong to label expressions of gender variance as symptoms of a mental disorder and that perpetuating DSM-IV-TR’s GID diagnoses in the DSM-V would further stigmatize and cause harm to transgender individuals. Other advocates in the trans community expressed concern that deleting GID would lead to denying medical and surgical care for transgender adults. This review explores how criticisms of the existing GID diagnoses parallel and contrast with earlier historical events that led APA to remove homosexuality from the DSM in 1973. It begins with a brief introduction to binary formulations that lead not only to linkages of sexual orientation and gender identity, but also to scientific and clinical etiological theories that implicitly moralize about matters of sexuality and gender. Next is a review of the history of how homosexuality came to be removed from the DSM-II in 1973 and how, not long thereafter, the GID diagnoses found their way into DSM-III in 1980. Similarities and differences in the relationships of homosexuality and gender identity to psychiatric and medical thinking are elucidated. Following a discussion of these issues, the author recommends changes in the DSM-V and some internal and public actions that the American Psychiatric Association should take.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; inégalités; premier cycle; psychiatrie; régions géographiques; santé; sciences; sciences humaines; sexologie; soc2014; système médical; systèmes d'oppressions; thématiques; transidentité; violences; états-unis

Butch/femme, F2M, pregnant man, tranny-boi: Gender issues in the lesbian community - Herbert, Sandra (Journal of Gay and Lesbian Mental Health, 2010)
The author discusses issues pertaining to transgender women and girls. Women identifying as male or transitioning to becoming male are often ignored in the scientific and lay literature on transgender people. The many newer terms for transgender women and girls are discussed, as well as new ways for transgender girls to express their identities. The importance of family and community supports is discussed, and common issues that young transgender people bring into mental health treatment are elucidated.
Keywords: amériques; discipline; identités LGBTQIA2+; médecine; personnes trans*; ressource en ligne; régions géographiques; santé; sciences; thématiques; états-unis